Price setting conduct in South Africa 2002-2007 : implications of microdata for monetary policy - Creamer, Kenneth (My University, 2011)
The objective of this research is to test the hypothesis that pricing conduct in South Africa, revealed by studies of pricing microdata, can be shown to have an impact on the modeling and conduct of monetary policy. In order to discern stylised facts about pricing conduct in South Africa, use is made of two unique microdata sets, which are the unit level basis of South Africa’s measured CPI and PPI over the period from December 2001 to December 2007. In particular, based on techniques which have been used in comparable studies in other countries, facts have been brought to light concerning inter alia the frequency of price changes, the magnitude of price changes, the duration of prices, heterogeneity in pricing, as well as evidence of seasonality, time-dependence and state-dependence in pricing conduct. In order to understand the implications of such pricing conduct, a basic closed economy theoretical model and thereafter an open economy New Keynesian DSGE model are used to compare the impact of various pricing assumptions. In general, but with some qualification regarding difficulties that arise in comparing pricing microdata with pricing conduct estimated in macro models, it is found that prices are more flexible than those estimated in the open economy DSGE model, implying sharper but less persistent interest rate responses to various shocks. Furthermore, the form of the New Keynesian Phillips curve used in the open economy DSGE model is found to be inconsistent with certain facts revealed through the price microdata.
Keywords: Pricing conduct; Price setting; Monetary policy; South Africa; Modelling